Diseño de un sistema fotovoltaico para riego de maíz en el sitio “Cuatro Lomas” del cantón Chaguarpamba - Lapo Motoche, Roque Mauricio (2023)
The present research work entitled "Design of a Photovoltaic System for Corn Irrigation in the Cuatro Lomas Site of Chaguarpamba (Loja-Ecuador)" aims to design and simulate a PV system for corn irrigation in the Cuatro Lomas site. This system will harness environmentally friendly energy to power the various components of the system and provide an alternative for irrigation purposes. To achieve this, an agronomic study was conducted to determine the evapotranspiration and net requirements of the corn crop in the area. Additionally, hydraulic design was carried out to analyze the best irrigation system for the site, determining that the most suitable option was sprinkler irrigation based on various technical characteristics such as topography, climate, soil type, etc. It was also calculated that a water flow rate of 3.72 m3/h is required for the specific crop and area, enabling the design of the irrigation system. This system mainly consists of sprinklers, storage tanks, a submersible pump, water distribution pipes, and other accessories. All these calculated data were validated through the use of EPANET software, which simulated the irrigation system and compared the results with the previously calculated data. Furthermore, the sizing of the photovoltaic system has been carried out to meet a demand of 6.15 kWh with a autonomy of up to 3 days without sunlight. This system will be composed of solar panels, batteries, and a controller. Keywords: photovoltaic system, corn irrigation, irrigation system, sprinkler irrigation, water flow, EPANET